Sematech : saving the U.S. semiconductor industry - Browning, Larry D. (Texas A & M University Press, 2000)
Annotation "In Sematech, Larry D. Browning and Judy C. Shetler trace the history of Sematech, a consortium formed by fourteen major American semiconductor manufacturers and the U.S. government. Sematech's founders were aware that consortia emphasizing cooperative research had been unsuccessful; Sematech planned a different approach. Its founding charter stated its goal: "To provide the U.S. semiconductor industry the capability for world leadership in manufacturing"--In other words, improve core manufacturing competence without making end products." "Browning and Shetler's history will inform and engage business historians, managers, public policy scholars, and others interested in the development and success of the U.S. computer chip industry and the application of its techniques to other fields of business."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Keywords: SEMATECH (Organization) -- History.; SEMATECH (Organization); Semiconductor industry -- Government policy -- United States.; Semi-conducteurs -- Industrie -- Politique gouvernementale -- États-Unis.; BUSINESS & ECONOMICS -- Infrastructure.; BUSINESS & ECONOMICS -- Corporate & Business History.; Semiconductor industry -- Government policy; United States; History